Confronting librarianship and its function in the structure of white supremacy and the ethno state - Sierpe, Eino (Journal of Radical Librarianship, 2019)
Rising socio-cultural and political tensions have helped increase awareness about long-standing structures of violence and abuse, as we have seen in the development and tumultuous expansion of the #MeToo movement. However, other significant conditions of injustice and oppression continue without drawing attention. This seems to be the case with the library profession. Despite strong and persistent links to white supremacy and a well-established record excluding minorities from its ranks, the library profession has been remarkably successful in nurturing an unassailable public image of virtuous liberal benevolence and near mythical devotion to the highest ideals of freedom, individual rights, and democracy. Its unsurpassed ability in evading scrutiny or criticism of any serious consequence while maintaining a strong record of dedicated service to white power is all the more remarkable at a time where social media is used to amplify campaigns against injustices or organizations believed responsible for conditions of oppression. Although Critical Librarianship, or #CritLib, is beginning to question some of the doctrinal assumptions underlying the practice of librarianship, an examination of some of the mechanisms with which white supremacy has been able to build an entire system of racial protectionism as an occupational sector that intersects with areas of significant public interest is an important and timely research concern.
Citation Key Alias: lens.org/069-727-951-165-240, pop00317
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found